(3efGbH GdEeGe GdCYXe CHh MfjaIs
(3ChdgG (B:s
(3Yf Ydi Hf CHj WGdH QVi Gddg Yfg bGd cfJ CfG haGWeI hGdMSf hGdMSjf QVi Gddg Yfge ai efRd QShd Gddg Udi Gddg Ydjg hSde aEPG PGc de jcf ai efRd QShd Gddg Udi Gddg Ydjg hSde eTF ef GdWYGe abGd Ydi QVi Gddg Yfg jG QShd Gddg s
(3BNQgG (B:s
(3aGYWGg CHG MfjaI hGNHQg HMOjK GdfHi Ydjg GdSdGe hCeQg HGcdg hMOg ceG CeQ GdfHi Udi Gddg Ydjg hSde aGcd CHh MfjaI MJi de jHb efg TMG Ke SeY CHh MfjaI Yf CfS QVi Gddg Yfg HYV CMGOjK SeYI Yf QShd Gddg Udi Gddg Ydjg hSde Ke bGe CfS QVi Gddg Yfg efs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B36s
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd Yf NdGa CHh jhSa heMeO CHG MfjaI QMege Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs